MESOZOIC O-TYPE ADAKITIC VOLCANIC ROCKS AND ITS PETROGENESIS, PALEO-TECTONIC DYNAMIC AND MINERALIZATION SIGNIFICANCE OF THE EASTERN SIDE OF SOUTHERN DA HINGGAN, CHINA - Zhang Y.B.; Sun S.H.; Mao Q. (My University, 2006)
The valley of Chagan Mulun River on the north side of Xila Mulun river in eastern Mongolian, is the east side of southern Da Hinggan Mesozoic volcano-platonic complex zone. Recently, many adakitic volcanic rocks with a little intergrowth of sodium rhyolite and basalt have been discovered in the Neo-mesozoic Manketou Obo volcanic group in this area. Of the adakite, Al2O3 > 15%, MgO < 3.4%, average K2O = 1.77 %, Na2O/ K2O > 1, LREE enriched, but HREE and LITE greatly depleted, lack negative Eu anomaly, high Sr (497.91 × 10-6 ~896.40 × 10-6), low Y(4.33 × 10-6 ~15.77 × 10-6 < 18 × 10-6), low Yb(O.35 × 10-6 ~1.54 × 10-6 < 1.9 × 10-6), ISr, = 0.70374 ~ 0.70594, ε Nd(t) = -0.45 ~ + 6.58. In K-Na-Ca, Rb-Sr-Ba, Sr/Y-Y and Sr/Yb-Yb diagram, all data of the rocks are distributed in adakitic region and show the evolution trend of trondhjemite. Therefore, those rocks are typical O-type adakites. Of those rocks with their intergrowths εNd(t), ISr, are close to that of Neo-paleozoic basalt, tDM(627 ~ 845Ma) of a part of adakite are the same of that (tDM = 627 -998Ma) of Neo-paleozoic subducted oceanic slab. Their Sr-Nd isotopic and Zr/Hf-Nb/ Ta ratios reveal the mixed feature of depleted mantle and lower crust, otherwise, a few adakite (tDM = 343 ~ 453Ma) are derived from younger mantle of Paleozoic. Hereby, infer that the source rocks are the lower crust of accretionary terrane consisted of multi-source materials dominated by Neo-Proterozoic subducted oceanic slab. LaN/YbN-YbN, and La/Sm-La diagram reveal that the adakitic magma was primitive magma created by source rocks partial melting via eclogite phase metamorphism, sodium rhyolite magmas were results of those primitive magma differentiation crystallization, but basalt should be created by deeply partial melting of the source rock. The petrochemical and trace elemental indicators show that those volcanoes were active in a continental marginal arc. This kind of arc and adakitic volcanic rocks appeared in Da Hinggan area in Mesozoic should be the result of that the remnant Paleoasia oceanic slab subducted down again along the surviving subduction zone to the lower crust of accretionary terrane and partially melted in Mesozoic. The mineralization of iron, copper and gold closely grown in this rock group is most likely to indicate a great prospect area.
Keywords: MINERALIZATION; O-TYPE ADAKITE; PALEOZOIC VOLCANIC ROCK; PETROGENESIS; SOUTHERN DA HINGGAN; TECTONIC DYNAMIC; Докембрий::Протерозой; Precambrian::Proterozoic